P–661 Comparative assessment of the structural features of human follicle-stimulating hormone in products from multiple markets. (6th August 2021) - Manzi, L; Colarusso, L; D'Angelo, F; Drovandi, D; Iozzino, L; Lanzoni, L; Migliaccio, W; Michaletti, A; Sepe, N; Lispi, M; Susana, M; Palmese, A
Abstract: Study question: The aim of the study is to explore the structural differences occurring in recombinant human follicle-stimulating hormone alfa (r-hFSH- α), originator and its biosimilars, from various countries. Summary answer: When compared with r-hFSH-α originator (Gonal-f), its biosimilars presented structural differences, namely Primapur showed a significant different glycosylation profile. What is known already: FSH is part of cystine knot growth factor superfamily and plays a central role in reproduction, as FSH stimulates follicular development and estrogen synthesis. R-hFSH- α is commonly used in assisted reproductive technologies to achieve multifollicular development. At the present r-hFSH- α biosimilars are available in Europe and other regions. R-hFSH-α is a complex glycoprotein, that possesses several structural features critical for its efficacy and safety1–2. Glycosylation profile is one of the most impactful attributes of the molecule defining a moiety of FSH isoforms with impact on its biological net effect3. Efficacy and safety of r-hFSH- α are strictly correlated with glycoforms' composition3–8. Study design, size, duration: At least two different batches of each r-hFSH- α originator and its biosimilars have been included in the study. Participants/materials, setting, methods: The structural features of products from six different marketed r-hFSH α (Gonal-f, Primapur, Folisurge Intas, Corneumon, Jin Sai Heng, Follitrope LG) have been investigated with a variety of analytical techniques in order to evaluate the presence of molecular differences, which could have a severe impact on the efficacy and safety of the product. The attributes which have been investigated in-depth include primary, secondary and tertiary structure as well as post-translational modifications (PTMs), including glycosylation and contaminants. Main results and the role of chance: All r-hFSH- α biosimilars analyzed presented differences compared to the originator. We firstly investigated Primapur and found significant differences regarding multiple structural attributes, particularly in the glycosylation profile. Gonal-f exhibited lower glycan branching, expressed by an A-index* of 2.5, while Primapur showed an A-index of 2.4. Furthermore, Primapur showed a lower level of sialylation in comparison with Gonal-f, as measured by their respective S-index* of 1.8 and 2.1. FSH glycosylation exhibits both macroheterogeneity and microheterogeneity, impacting both FSH protein's half-life and affinity with the follicle-stimulating hormone receptor (FSHR). Antennarity, representing FSH microheterogeneity, influence r-hFSH-α activity since it has been shown that bulky and extended glycans may take longer to fit into the FSHR cavity compared to less sterically hindering glycans, resulting in a delayed response 7, 8.Additionaly, sialylation has been shown in-vivo to correlate with plasma half-life and effect on granulosa cells proliferation 1, 2, 3. The slower clearance of highly sialylated r-hFSH has been shown to lead to a higher in-vivo activity, despite the lower in-vitro bioactivity 1, 2, 3. *A-index and S-index express respectively a measure of the number of antennae and sialic acid per glycan. Final values are generated from many relative abundances normalized to 100, highlighting the significance of small numerical differences. Limitations, reasons for caution: More batches should be tested for each product. The authors are presenting full characterization of only one of the biosimilars since the rest of the products are under characterization. Wider implications of the findings: r-hFSH-α originator and its biosimilar showed differences in terms of glycosylation profile that is well known as the major protein characteristic impacting FSH activity as extensively demonstrated in in-vivo and in-vitro models. This structural difference could have impact also on product efficacy and safety. Trial registration number: 'not applicable'